Depression Anxiety Stress Scales-21: Measurement and Structural Invariance Across Ratings of Men and Women. (August 2014) - Gomez, Rapson; Summers, Mathew; Summers, Avril; Wolf, Anna; Summers, Jeff
The current study examined the measurement and structural invariance of the Depression Anxiety Stress Scales-21 (DASS-21) across ratings provided by men ( N = 227) and women ( N = 460). Multiple-group confirmatory factor analysis (CFA) supported full metric invariance and intercepts invariance for 20 of the 21 items. Invariance for all item intercepts was supported by multiple indicators multiple causes (MIMIC) procedure that controlled for the effects of age. Multiple-group CFA supported invariance for all factor variances and covariances. This procedure and the MIMIC analyses found equivalency for all latent mean scores. These findings indicate good support for measurement and structural invariance of the DASS-21 rating across men and women. The psychometric and practical implications of the findings are discussed.